SYZYGIUM AROMATICUM (L.) EXTRACTS STIMULATE THE CELL PROLIFERATION IN AN IN VITRO SCRATCH ASSAY - R. Mumtaz; M. A. Khan; T. Mubeen; M. Azeem; M. Zubair (Journal of Animal and Plant Sciences, 2023)
Wounds have always been a serious hazard to the public health around the world. Currently available treatments are limited due to their side effects and high cost. Plants are being used as a good source of medicines due to their safety, and ease of access.The objective of the study was to examine the potential cell proliferation and migration activities of Syzygium aromaticum extracts to understand the wound healing property of this plant. Methanol-, ethanol- and acetone-based extracts were prepared from S. aromaticum flower buds and tested in a scratch assay using a human retinal pigment epithelial (RPE) cell line. Polyphenolic contents in the extracts of S. aromaticum responsible for wound healing potential were identified using high performance liquid chromatography (HPLC). The study revealed that the majority of examined extracts stimulated cell proliferation of RPE cells. The activities were highest when the extracts were prepared using acetone as solvent at 0.05 mg/mL concentration. Acetone- and ethanol-based extracts yielded the best results at 0.05 mg/mL whereas methanol-based extract produced the highest result at 0.5 mg/mL. Thus, the present study provides better understanding of the traditional use of S. aromaticum for the treatment of wounds. However, further detailed studies are needed to optimize the concentration of different compounds of S. aromaticum for wound healing treatment.
Keywords: Bioactive compound; Cell scratch assay; Polyphenol; Traditional medicine